Current topics in technology : social, legal, ethical, and industry issues for computers and the Internet - Paparella, Maureen Sheehan; Simko, Eugene (Course Technology, Cengage Learning, 2010)
This collection of thirty articles addressing the latest trends in technology encourages classroom discussion and raises student's awareness of the important role that technology plays in both personal and professional areas